Brand love as mediator of the brand experience-satisfaction-loyalty relationship in a retail fashion brand - Ferreira, Pedro (2019)
Framed by the consumer-brand relationship theory, this paper investigates the path from the brand-consumer behaviour interaction to the relationship durability and stability, through brand relationship quality. Specifically, it examines brand experience as an antecedent of brand love, and customer loyalty and satisfaction as outcomes in the retail setting. Based on 560 customers’ responses to a face-to-face questionnaire administered in a fashion brand retail store, research hypotheses were tested using a structural equation model. The findings suggest that brand experience influences brand love, with a higher incidence of sensory and affective dimensions. Brand love, in turn, influences customer loyalty, both directly and indirectly through customer satisfaction. This research contributes to the still understudied relation between brand experience and brand love in the retail context and to the need to understand the satisfaction-loyalty relation involving other variables as predictors. Nevertheless, results are limited to one specific retail fashion brand and generalizations should be taken carefully.